2015
DOI: 10.1186/s12942-015-0025-5
|View full text |Cite
|
Sign up to set email alerts
|

Geographic disparities in late stage breast cancer incidence: results from eight states in the United States

Abstract: BackgroundLate stage of cancer at diagnosis is an important predictor of cancer mortality. In many areas worldwide, cancer registry systems, available data and mapping technologies can provide information about late stage cancer by geographical regions, offering valuable opportunities to identify areas where further investigation and interventions are needed. The current study examined geographical variation in late stage breast cancer incidence across eight states in the United States with the objective to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 28 publications
0
25
1
3
Order By: Relevance
“…Unlike studies that used Medicare SEER data and detected survival disparities by income level among older women [5254], we did not find that low SES predicted worse outcomes. Although the reasons for this different finding are unclear, it is possible that lower SES women who are younger and commercially insured have better access to screening and care than older, Medicare insured women with lower SES.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike studies that used Medicare SEER data and detected survival disparities by income level among older women [5254], we did not find that low SES predicted worse outcomes. Although the reasons for this different finding are unclear, it is possible that lower SES women who are younger and commercially insured have better access to screening and care than older, Medicare insured women with lower SES.…”
Section: Discussioncontrasting
confidence: 99%
“…This is compared to Seattle, where 31 % of VS are less than 1 cm in size while only 15 % are greater than 3 cm in size. The association between geography and stage of disease at presentation and/or treatment selection has been seen with several other disease processes [31][32][33][34]. Explanations for such findings include local and regional inequalities in medical care access, differences in public assistance programs, racial and socioeconomic disparities, and variance…”
Section: Discussionmentioning
confidence: 91%
“…1). in population education levels [31][32][33][34][35][36][37]. Hypothesizing that rural areas carry a higher risk of late disease presentation, we sought to determine whether decreasing population density was associated with older age or larger tumor size at diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, it was reported that the incidence of breast cancer among AA women is almost equal to that of non‐Hispanic White women . The racial inequality in breast cancer survival has been attributed to several factors, such as socioeconomic status , geographical barriers to breast care , and treatment . Furthermore, AA women are more likely to be diagnosed with aggressive basal‐like breast tumors that are hormone receptor‐negative and that are associated with poorer breast cancer survival compared to other ethnic groups.…”
Section: Introductionmentioning
confidence: 99%